Drought phenomena versus water supply systems - Miszta-Kruk, Katarzyna; Kaznowska , Ewa (Instal, 2019)
One of the current challenges in water management is the rising occurrence of droughts in recent years. The negative consequences of this phenomenon relate to many aspects of life and economy. Long-term lack of rain and high air temperatures cause the deterioration of water quality and reduce their quantity, possible to be used for public supply. This applies to the level of surface water and groundwater. This article presents the problem of the impact of the drought phenomenon on water supply in water supply systems, particularly noticeable in small and medium-sized cities.